Pemberdayaan Komunitas Guru di SDN 2 Karanganyar Gunung melalui Kegiatan Deep Learning dalam Pembelajaran IPA - Patonah, Siti; Indiati, Intan; Artharina, Filia Prima (Universitas Negeri Makassar, 2025)
The implementation of the deep learning approach still requires a lot of effort, especially for elementary school teachers for science subjects. The solution to the problems faced is to provide assistance for teachers to learn, design, and implement deep learning approaches in the classroom. The activity method used is Participatory Action Research (PAR), participants/partners are involved in the entire activity through 4 stages, namely: analysis of partner needs, preparation, implementation, evaluation and follow-up. The results of this activity are: 1) as many as 68.75% of participants have a high and stable understanding, 18.75% actually experience a decrease and only 12.5% experience an increase, 2) an item about